PHYSICAL CHARACTERISTICS OF ICE CREAM WHICH REPLACED MILK POWDER WITH DIFFRENT CEREALS FLOUR - Ghanim Hasan; Saja M. Kassem (Mesopotamia Journal of Agriculture)
The aim of this study was to know the effect of partial or total substitution of dry skim milk in ice milk mixtures by using different cereals flour of oat. barley and corn treatments were prepared by substitution of 0, 25, 50, 75 and 100% from dried skim milk. In the other treatment, 0.1% of cinnamon and ginger were used to conceal or cover undesirable flavors and to use them as antibacterial agents.  Results show that specific weight was increased in all samples contained cereal flours compared with control sample.  The highest values were 1.1178 and 0.9874 for mixtures and product respectively of samples contained oat flour of 100% substitution and the lowest values were in mixture contained corn flour. The relative viscosity was increased in mixtures with increasing of substitution compared with control sample. The highest viscosity value (21.607) was in sample substituted 100% oat flour. whereas the lowest value (18.160) was in sample substituted with corn flour. The agitating ability was decreased with increasing of substitution. in which the lowest agitating ability was in samples substituted wit oat flour and the highest was in samples substituted with corn flour. The revenue percent was decreased in ice cream product of samples substituted with cereal flours compared with control sample and the decreasing was continued with increasing of substitution percent. The revenue percent was the lowest (62.173) in samples substituted with 100% oat flour. Shrinkage percent was decreased in samples substituted with cereal flours. Freezing point was also decreased with increasing of substitution in which the lowest value was -1.777 ºC for the sample substituted with 100% oat flour. Concerning melting point. the samples substituted with oat flour was more resist to melting followed by corn flour.